A Study of the Far Infrared Spectrum of N-Acetyl-D-Glucosamine Using THz-TDS, FTIR, and Semiempirical Quantum Chemistry Methods - Pedro Chamorro-Posada; Iosody Silva-Castro; José Vázquez-Cabo; Pablo Martín-Ramos; José María López-Santos; Jesús Martín-Gil (Journal of Spectroscopy)
The far infrared spectrum of N-acetyl-D-glucosamine has been studied by combining THz–TDS and FTIR characterization techniques with theoretical studies based on semiempirical quantum chemistry methods. A strong spectral peak at 60 cm−1 has been identified, which constitutes the main signature of the material in the terahertz band. Calculated molecular vibrations are in good qualitative and semiquantitative agreement with both the THz-TDS and FTIR experiments. In comparison to previous DFT-based studies, the semiempirical approach chosen herein, suitable for parallel multi-core and GPU acceleration, allows for a full study using periodic boundary conditions and no further approximations within a constrained computing time.